AGRICULTURE AND ITS CONTRIBUTION FROM THE ISLAMIC ECONOMICS PERSPECTIVE (Sains Humanika, 2009)
This article explains the concept of agriculture in Islam and its contributions towards human and Muslim ummah from the perspective of Islamic economics. This article is divided into four sections namely agriculture in Islam, concept of an idle land, definitions of an idle land from four famous schools of Islamic jurisprudence as well as the contribution of agriculture towards human and muslim ummah in terms of human civilization, security and supply of food, contribution through tithe (zakat) payment made by farmer and agro entrepreneur, and also contribution of agriculture in accomplishing and executing specific religious worships (‘Ibadat) in Islam that can be done by participating in this sector.
Keywords: Agriculture; idle land (Ihya' al'Mawat); human civilization; food supply; Zakat; ‘Ibadat